A INCLUSÃO SOCIAL E AS MEDIAÇÕES NA RECEPÇÃO DA COMUNICAÇÃO MERCADOLÓGICA TELEVISIVA POR PESSOAS COM DEFICIÊNCIA VISUAL - Haase, Catherine da Silva (2014)
This study reflects and looks at impacts of T.V commercial on visually impaired individuals. Also, it further investigates the incentives and perception given to this subject by government and private sector. The study is based on the Theory of Mediation, which is studied by scholars of Etudies of the Reception, to understand how visually impaired interact with different categories of T.V commercials and their impacts on individuals values, world perception and their own living conditions. The adapted methodology for this study is based on actual field work of qualitative nature, interviews, use of data sets and studies. The paper concludes that the living reality is far from what is commonly believed and it seems that these people are least likely considered as target audience. We need to improve the overall awareness of society and take measures to improve the present scenario through bridging the gap between T.V commercials and visually impaired. Keeping the present scenario in mind, the thesis presents suggestions within the communication framework that can act as a social agent and bring significant visible changes in the lives of visually impaired.